Comparative Evaluation of Dexmedetomidine and Magnesium Sulphate on Propofol Consumption, Haemodynamics and Postoperative Recovery in Spine Surgery: A Prospective, Randomized, Placebo Controlled, Double-blind Study - Vinit K. Srivastava; Abhishek Mishra; Sanjay Agrawal; Sanjay Kumar; Sunil Sharma; Raj Kumar (Tabriz University of Medical Sciences, 2016)
Purpose: Dexmedetomidine and magnesium sulfate have been used in anesthesia as adjuvant to provide hemodynamic stability and anesthetic agents sparing effect. We compared these effects of dexmedetomidine and magnesium sulfate in spine surgeries. Methods: Ninety patients were randomly assigned to three groups. Group D received dexmedetomidine loading dose 1 µg/kg over a period of 15 minutes and maintenance 0.5 µg/kg/h throughout the surgery. Group M received magnesium sulfate loading dose 50 mg/kg over a period of 15 minutes and maintenance 15 mg/kg/h throughout the surgery. Group C received same volume of normal saline. Heart rate (HR) and blood pressure values were recorded at various intervals. The induction and maintenance doses of anesthetics and recovery parameters were also recorded. Results: Heart rate in group D and group M were significantly decreased (p<0.05) during the whole intraoperative period compared to preoperative values. There was a significant difference in HR values between group C, D and M, during the whole intraoperaive period (p<0.05). Blood pressure values were statistically significantly lower in the group D and group M compared to group C after intubation and all time observations of surgery (p<0.05). Both drugs reduced the anesthetic agent's requirement during surgery. However, the recovery parameters were statistically significant increase with magnesium sulphate compared to dexmedetomidine and control groups. Conclusion: Dexmedetomidine is more effective than magnesium sulfate for maintaining the hemodynamic stability in spine surgeries. Both these drugs also reduce the requirements of anesthetic agents. Recovery from dexmedetomidine is as rapid as control group compared to magnesium sulfate.